Middle Stone Age foragers resided in high elevations of the glaciated Bale Mountains, Ethiopia - Ossendorf, Götz; Groos, Alexander R.; Bromm, Tobias; Tekelemariam, Minassie Girma; Glaser, Bruno; Lesur, Joséphine; Schmidt, Joachim; Akçar, Naki; Bekele, Tamrat; Beldados, Alemseged; Demissew, Sebsebe; Kahsay, Trhas Hadush; et al. (Science (American Association for the Advancement of Science), 2019)
Studies of early human settlement in alpine environments provide insights into human physiological, genetic, and cultural adaptation potentials. Although Late and even Middle Pleistocene human presence has been recently documented on the Tibetan Plateau, little is known regarding the nature and context of early persistent human settlement in high elevations. Here, we report the earliest evidence of a prehistoric high-altitude residential site. Located in Africa’s largest alpine ecosystem, the repeated occupation of Fincha Habera rock shelter is dated to 47 to 31 thousand years ago. The available resources in cold and glaciated environments included the exploitation of an endemic rodent as a key food source, and this played a pivotal role in facilitating the occupation of this site by Late Pleistocene hunter-gatherers.